2013
DOI: 10.1111/tbj.12223
|View full text |Cite
|
Sign up to set email alerts
|

ER and PR Immunohistochemistry and HER2 FISH versus Oncotype DX: Implications for Breast Cancer Treatment

Abstract: Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor (HER2) concordance between immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), and Oncotype DX, a commercially available RT-PCR-based assay which recently began reporting biomarker results was assessed. ER concordance was 98.9% (262/265), Pearson correlation coefficient (r) = 0.42, and Spearman's rank correlation (ρ) = 0.25. Positive percent agreement for ER was 98.9% (262/265). One patient with discorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
6
30
0
1
Order By: Relevance
“…There has been growing interest in molecular biomarker testing by RT-PCR with conflicting results [1520]. In our study, ER displayed a very high concordance of 98.8% between IHC and RT-PCR, in accordance with the literature (93% to 100%).…”
Section: Discussionsupporting
confidence: 91%
“…There has been growing interest in molecular biomarker testing by RT-PCR with conflicting results [1520]. In our study, ER displayed a very high concordance of 98.8% between IHC and RT-PCR, in accordance with the literature (93% to 100%).…”
Section: Discussionsupporting
confidence: 91%
“…10 Over the years, the measurement of RNA for breast cancer markers has emerged using several commercially available platforms 2224 , most significantly for multi-parameter prognostic testing. However simple qRT-PCR has failed to gain acceptance for HER2 assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Oncotype DX RS is predictive of patient's benefit from adjuvant chemotherapy in both the low and high RS categories based on the rate of distant recurrence at 10 years. However, the data and suggested treatment strategy for intermediate RS patients are less clear and will likely remain so until the results from the Trial Assigning IndividuaLized Options for Treatment (TAILORx) trial become available [24]. When weighing the treatment options for the patients in the intermediate RS category, the PR status may be an important factor to consider in clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…For ER, the concordance between central IHC and RT-PCR was 93%, whereas for PR the concordance was 88%. Park et al [24] reported 98.9% concordance for ER and 91.3% concordance for PR when IHC and RT-PCR were compared in 265 breast cancer patients. In another study of 464 breast cancer cases, comparison of hormone receptor status reported by IHC and RT-PCR showed a good concordance of 98.9% for ER and 94.2% for PR status [28].…”
Section: Discussionmentioning
confidence: 99%